Tingkat Kerusakan Tanaman Seledri Akibat Nematoda Puru Akar (Meloidogyne spp.) Di Landasan Ulin Utara Kota Banjarbaru - Yanti, Dewi Dhea; Fitriyanti, Dewi; Marsuni, Yusriadi (www.ulm.ac.id, 2025)
The celery plant (Apium graveolens L.), is a vegetable with economic value that is typically used to flavor food, add spices to dishes, and decorate dishes. In cultivating celery plants, there is one obstacle in its cultivation, namely interference from Root Knot Nematodes (RKN). Root Knot Nematode (RKN) is a disease that causes damage to celery plants. This research aims to determine the level of damage to celery plants caused by root knot nematodes (Meloidogyne spp.) in Sukamaju Ujung Landasan Ulin Utara Village. Sampling of celery plants infected with root knot nematodes was carried out using a purposive sampling method in a farmer's field in Sukamaju Ujung Landasan Ulin Utara Village. The results of the study showed that the level of damage to celery plants caused by root knot nematodes was high, this was indicated by the intensity of damage (72,8%) and severity of disease (58.3%) and the number of populations in the root network is (138.6) nematodes and the population in soil extraction was (217.3) nematodes.